2012
DOI: 10.18438/b88p6d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Based Medicine Teaching in Undergraduate Medical Education: A Literature Review

Abstract: the terms of the Creative Commons-AttributionNoncommercial-Share Alike License 2.5 Canada (http://creativecommons.org/licenses/by-nc-sa/2.5/ca/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjectives -To determine the year when evidence based medicine (EBM) was introduced and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A number of other studies have shown positive students' preference of EBM. Currently, it has become a commonly addressed topic (Ilic & Forbes 2010;Mi 2012) and a requirement in all postgraduate training programs in Saudi Arabia.…”
Section: Educational Contentmentioning
confidence: 99%
“…A number of other studies have shown positive students' preference of EBM. Currently, it has become a commonly addressed topic (Ilic & Forbes 2010;Mi 2012) and a requirement in all postgraduate training programs in Saudi Arabia.…”
Section: Educational Contentmentioning
confidence: 99%
“…During clerkship, students were reminded of the importance of teaching-learning in problem solving (24), which is of particular interest, mainly in the performance of clinical tasks of the medical profession, as well as in the development of "learning styles" skills, internet, database consulting, literature and audiovisual methods, as well as inherent cognitive critical analysis (25,26). The importance of this methodology justified its inclusion in the medical curriculum (27).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…There were systematic reviews that analyzed general information literacy skills training in the health sciences and the most effective methods for teaching information literacy skills to undergraduate students [12,44,45], but these studies did not address EBP instruction or directly focus on the role of the librarian in teaching EBP. Other literature reviews summarized EBM instruction in undergraduate medical education but excluded other health professional students and did not discuss the role of the librarian in teaching EBM [46,47].…”
Section: Discussionmentioning
confidence: 99%